Plant Parasitic Nematodes in Subtropical and Tropical Agriculture 2005
DOI: 10.1079/9780851997278.0053
|View full text |Cite
|
Sign up to set email alerts
|

Methods for extraction, processing and detection of plant and soil nematodes.

Abstract: This paper presents the most common methods for extracting (including Baermann funnel, mistifier, maceration, sieving, elutriation and flotation techniques), processing, examining (handling and fixing) and detecting plant and soil nematodes. Some molecular techniques (e.g. DNA extraction, PCR, sequencing and amplified fragment length polymorphism) available for detection and identification of nematodes are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
205
0
17

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(224 citation statements)
references
References 0 publications
2
205
0
17
Order By: Relevance
“…In order to observe RKN penetration, localization and subsequent development within the roots, fine root tips were stained with acid fuchsin, according to Byrd et al (1983) and Hooper et al (2005), then observed by stereomicroscopy (Leica MZ75) and bright-field light microscopy (Zeiss Axiophoto). Root segments were also embedded in resin for sectioning (4 lm).…”
Section: Histopathological Analysismentioning
confidence: 99%
“…In order to observe RKN penetration, localization and subsequent development within the roots, fine root tips were stained with acid fuchsin, according to Byrd et al (1983) and Hooper et al (2005), then observed by stereomicroscopy (Leica MZ75) and bright-field light microscopy (Zeiss Axiophoto). Root segments were also embedded in resin for sectioning (4 lm).…”
Section: Histopathological Analysismentioning
confidence: 99%
“…Extracción de nematodos de suelo y raíces: la extracción de nematodos de suelo se realizó mediante el método de Baermann modificado (Hooper et al 2005). Se pesaron 100 g de suelo y se colocaron en un filtro de papel toalla que estaba extendido sobre un tamiz dentro de un recipiente.…”
Section: Análisis De Suelo Nematodos Y Datos Pluviométricosunclassified
“…La extracción de nematodos de raíces se realizó mediante el método de macerado y filtrado (Hooper et al 2005). Se pesaron 25 g de raíces y se colocaron en una licuadora con 200 ml de agua, seguidamente se licuó por 30 segundos.…”
Section: Análisis De Suelo Nematodos Y Datos Pluviométricosunclassified
“…To reach the planned Meloidogyne infestation, 20 g infested soil with pieces of galled roots were placed under the roots of tomato plants during planting. (For the Meloidogyne infestation not J2 nematodes (Hooper et al 2005) were used, because our opinion was that although the number of nematodes are known in that way, but the juveniles can get easily injured during the extraction process. Therefore they may lose their virulence.…”
Section: Interaction Experimentsmentioning
confidence: 99%